Zinc Protoporphyrin-9 Potentiates the Anticancer Activity of Dihydroartemisinin - Yu Zhang; Xu Zhang; Bing Zhou (MDPI AG, 2023)
Besides the clinically proven superior antimalarial activity, artemisinins (ARTs) are also associated with anticancer properties, albeit at much lower potency. Iron and heme have been proposed as possible activators of ARTs against cancer cells. Here we show that zinc protoporphyrin-9 (ZnPPIX), a heme homolog and a natural metabolite for heme synthesis during iron insufficiency, greatly enhanced the anticancer activity of dihydroartemisinin (DHA) in multiple cell lines. Using melanoma B16 and breast cancer 4T1 cells, we demonstrated ZnPPIX dramatically elevated intracellular free heme levels, accompanied by heightened reactive oxidative species (ROS) production. The tumor-suppression activity of ZnPPIX and DHA is mitigated by antioxidant vitamin E or membrane oxidation protectant ferrostatin. In vivo xenograft animal models confirmed that ZnPPIX significantly potentiated the tumor-inhibition capability of DHA while posing no apparent toxicity to the mice. The proliferating index and growth of tumors after the combinatory treatment of DHA and ZnPPIX were evidently reduced. Considering the clinical safety profiles of both DHA and ZnPPIX, their action synergy offers a promising strategy to improve the application of ARTs in our fight against cancer.